Experiment to measure the Lamb shift in muonic hydrogen - Pohl, R. (2000)
Abstract The contribution of the root mean square (RMS) proton charge radius to the Lamb shift (2S–2P energy difference) in muonic hydrogen (µp) amounts to 2%. Apart from the uncertainty on this charge radius, theory predicts the Lamb shift with a precision on the ppm level. We are going to measure ?E (2 S1/2(F=1)–2 P3/2(F=2)) in a laser resonance experiment to a precision of 30 ppm (i.e., 10% of the natural linewidth) and to deduce the RMS proton charge radius with 10-3 relative accuracy, 20 times more precise than presently known. The most important requirement for the feasibility of such an experiment, namely the availability of a sufficient amount of long lived metastable µp atoms in the 2S state, has been investigated in a recent experiment at PSI. Our analysis shows that in the order of one percent of all muons stopped in low pressure hydrogen gas form a long lived µp(2S) with a lifetime of the order of 1 µs. The technical realization of our experiment involves a new high intensity low energy muon beam, an efficient low energy muon entrance detector, a randomly triggered 3 stage laser system providing the 0.5 mJ, 7 ns laser pulses at 6.02 µm wavelength, and a combination of a xenon gas proportional scintillation chamber (GPSC) and a microstrip gas chamber (MSGC) with a CsI coated surface to detect the 2 keV X rays from theµp(2P ? 1S) transition.